Default Mode Network as the Neurophysiological Groundwork of Collectivity - Ceylan, Mehmet Emin; Kaya Yertutanol, Fatma Duygu; Dönmez, Aslıhan; Önen Ünsalver, Barış (Journal of NeuroPhilosophy, 2024)
All newborns are born with a collective self that carries the traces of the selves of all humans who lived before them, and then form their individual self over the collective self in the light of the experience and information they gathered by themselves. This library of knowledge in question can be reached for a short time during sleep and mind-wandering. Easy access to this great source of knowledge requires that the archive in question is recorded in a neural network that has widespread projections in the brain. In our opinion, the best candidate for this is default mode network due to its neurophysiological and neuroanatomical characteristics. In this article, default mode network is discussed as a dynamic neural archive, which carries all the knowledge of humanity and the concept of collectivity is discussed with a philosophical point of view on the basis of neuroscience.